تعديل الخلائط البيتومينية الإسفلتية المستخدمة في محافظة اللاذقية بالمطاط المدور من إطارات السيارات - رناء درويش أحمد; رامي حنا; فاتن فوز (Tishreen University, 2014)
يهدف البحث إلى دراسة إمكانية تعديل الخلطات الإسفلتية المستخدمة في مدينة اللاذقية بالمطاط المدور من إطارات السيارات المطاطية المستهلكة، وذلك لتحسين أدائها. لقد أظهرت أبحاث عديدة حول العالم جدوا استخدامها. شمل البرنامج الاختباري لهذا البحث استخدام بيتومين (60-70) ومطاط ناتج من تدوير الإطارات المطاطية التالفة الناتجة عن العربات السياحية وبعمر أقل من 5 سنوات ، علماً أنه تم استخدام تركيبين حبيين من أقطار حبيبات فتات المطاط وبنسب وزنية مختلفة (5-10-15)% و (2-3-4-5)‰ من البيتومين, وتم استخدام جهاز (ARMATEST) في عملية مزج فتات المطاط مع البيتومين وفق بارامترات محددة . كما أجريت مجموعة من التجارب لتحديد خواص البيتومين المعدل بالمطاط المدور وغير المعدل ، وتم تصميم خلطات بيتومينية عند نسب مختلفة من المطاط ، ومن ثم عولجت نتائج التجارب باستخدام برنامج الإكسل. لقد بينت التجارب أنه ومع زيادة نسبة المطاط يتناقص الغرز والاستطالة وترتفع نقطة التميع ، كما أظهرت الخلائط الإسفلتية المعدلة بالمطاط  زيادة في الثبات ونقصان في الانسياب عن الخليط غير المعدل. The aim of this research to study the possibility of modification of asphalt mixtures used in the city of Lattakia from recycled rubber tires, rubber consumingto improved its performance which  research showed that many around the world on the feasibility of their use. Theexperimental program included the test for this search using bitumen (60-70) and the output of recycled rubber tire damaged caused by tourist vehicles and under the age of 5 years, knowing that we used two different aggregate grading of diameters granulated rubber crumbs and different ratios grains (5-10-15)% and (2-3-4-5)‰of bitumen . It was the use of a (ARMATEST) in the process of blending bitumen with rubber crumbs according to specific parameters and conducted a series of experiments to determine the properties of recycled rubber modified bitumen and unmodified bituminous mixtures were designed when different ratios from rubber additives and processed the results of experiments using the Excel program. Experiments showed that with the increase in the proportion of rubber the penetration and ductility decreased and softening point rise , showed rubber-modified asphalt mixtures increase in stability and decrease in the flow rate from the mixture of others.